The characteristics of mothers and stunted children in Kricak, Tegalrejo, Yogyakarta - Maulita Listian Eka Pratiwi; Chandra Retno Fianti (Universitas 'Aisyiyah Yogyakarta, 2020)
Stunting on children is pressing matters since it could prevent and, up to a point, impair the physical and mental development of children, the growth of the brain, intelligence, and metabolism. Furthermore, in the long term it is worried that it could lead to the decrease of the cognitive ability and learning achievement, as well as the immunity so that the children will be prone to high-risk degenerative illness, old age disability, uncompetitive work competence, and low rate of productivity in economy (Kementrian Kesehatan, 2016). The aim of the research is to comprehend the character of stunted mothers and children (24-59 months) in Kricak village. The research applies analytic-descriptive model as the research design and cross-sectional study as the approach. The population in the research is 76 mothers in Kricak village having stunted children aged between 24 and 59 months. The instruments of the research are checklists and KIA books. Based on the research, the number of stunted children aged from 24 to 59 months were 76 children consisting of 69 stunted children (90,8%) and 7 severely stunted children (9,8%) and, mostly, it was suffered by the children coming from low-income families, namely 44 families (54,3%).